2003
DOI: 10.1001/archinte.163.20.2433
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Pain Comorbidity

Abstract: Because depression and painful symptoms commonly occur together, we conducted a literature review to determine the prevalence of both conditions and the effects of comorbidity on diagnosis, clinical outcomes, and treatment. The prevalences of pain in depressed cohorts and depression in pain cohorts are higher than when these conditions are individually examined. The presence of pain negatively affects the recognition and treatment of depression. When pain is moderate to severe, impairs function, and/or is refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

126
2,301
12
94

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,954 publications
(2,533 citation statements)
references
References 158 publications
126
2,301
12
94
Order By: Relevance
“…For instance, a biologic link between depression and pain is plausible, although not completely understood, as these conditions share common biologic pathways and neurotransmitters, such as serotonin and norepinephrine (4). A deficiency of these neurotransmitters is expected to affect both mood and pain thresholds, possibly explaining the relationship between depression and LBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a biologic link between depression and pain is plausible, although not completely understood, as these conditions share common biologic pathways and neurotransmitters, such as serotonin and norepinephrine (4). A deficiency of these neurotransmitters is expected to affect both mood and pain thresholds, possibly explaining the relationship between depression and LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Depression, whether clinically diagnosed by a health practitioner, or as self-reported depressive symptoms, is commonly seen in patients with low back pain (LBP) (4), which is also a highly prevalent, costly, and disabling condition (3). The direct health costs of LBP are higher in patients with depression and usually associated with more complex diagnostic and treatment approaches, commonly involving the engagement of multiprofessional teams and use of tertiary pain specialist clinics, leading to higher costs and rates of health care utilization (5).…”
Section: Introductionmentioning
confidence: 99%
“…First, elevated preoperative depressive symptoms have been shown to be prognostic of worse patient postoperative pain and poorer function [5,6,12,17]. High levels of depressive symptoms likely make a challenging postoperative recovery even more difficult for patients and there is a moderate association between depression and pain [1,7]. High preoperative depressive symptom scores also may indicate a high patient risk of worse pain and function after surgery because of poor coping skills and a reduced ability to deal with the challenges of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…It reduces pain tolerance and threshold, increases analgesic requirements, and is associated with poor adherence to therapy (9,10). A crosssectional study of patients with recently diagnosed EIP found that 23% of patients screened positive for depressive symptoms (11).…”
Section: Introductionmentioning
confidence: 99%